Inconsistencias de la cláusula de bloqueo en el convenio de accionistas a la luz de la legislación ecuatoriana actual - Piñeiros Espinosa, César Miguel (2017)
Agreements of Shareholders, is known as the kind of agreement between partners of a company, in order to supplement, modify or anticipate adverse situations to enforce their will and which do not appear within the social contract, and it is considered one of the best ways to complement matters related to commercial societies. Among these agreements, we have the blocking clause, which is nothing more than an agreement to stop actions of other partners, whether these are for sale, transmission or modes that will be made on the right of actions. However, in Ecuador this topic has several inconsistencies, making it difficult to understand the legal effects and the validity of agreeing a blocking clause within the Agreements of Shareholders.